Late‐onset heart failure after treatment for breast cancer. Issue 1 (27th August 2019) - Ewer, Steven M.; Pham, David D.
Abstract : Late‐onset heart failure after breast cancer is a rare event. It is necessary to remain vigilant for cardiac complications after potentially toxic cancer treatments.